Strategy and Function of Perfect Health's Public Relations Activities in Enhancing a Positive Image through Philanthropic Corporate Social Responsibility - Geofakta Razali; Rizki Hidayat (Ikatan Sarjana Komunikasi Indonesia, 2022)
Efforts to reduce poverty rate are still a highlighted issue almost in every country. Especially during the COVID-19 pandemic, there is increasing attention to corporate social responsibility (CSR) around the world, to find out the magnitude of its influence on corporate image as can be seen from its Â sustainable, accountable and transparent implementation. Perfect Health carries out several strategies to realize Â the function of Public Relations activities through CSR Philanthropy in the program